The Slippery Slope U.S. Military moves into México - Willson, Brian (Estados Unidos | ESTADOS UNIDOS Bill Moto veterans of foreign wars/Santa Cruz California, 1997)
On February 9, 1995, while traveling south on curvy, mountainous Chiapas Highway 173, we encountered a long, heavily supplied Mexican military convoy, carrying hundreds of armed soldiers. Among the new uniforms and equipment, I believed I recognized U.S. materiel, armored personnel carriers among them. The convoy moved north towards Simojovel, the highland’s village we had just left. Later I learned that we had seen the beginning of a major military offensive which ravaged many communities, and whose goal was the capture of Zapatista leaders
Sin Especificar
Keywords: Ofensiva Militar | Guerra civil